It looks like there is a slight misplacement of the equal sign in your expression. Let's correct it. If you meant the equation to be:
3(2k + 30) - (3k - 5) = 6
then we can find the solution for k. Let's first simplify the equation by distributing the 3 into (2k + 30) and then solving for k:
3(2k + 30) - (3k - 5) = 6
6k + 3 * 30 - 3k + 5 = 6 (Note: distribute the negative sign across the (3k - 5))
6k + 90 - 3k + 5 = 6
3k + 95 = 6
Now, let's isolate the term with k:
3k = 6 - 95
3k = -89
Finally, divide both sides by 3 to solve for k:
k = -89 / 3
So the solution for k is:
k = -89 / 3
k = -29.666... or -29 and 2/3
If you meant a different equation, please clarify the expression, and I'll help you solve it.
What is the solution to 3(2k+30=6 - (3k-5)?
1 answer